Sensing, seizing and reconfiguring: Understanding wine tourism development in emerging economies through the dynamic capabilities approach - Duarte Alonso, Abel; Kok, Seng (Cognizant Communication Corporation, 2020)
In exploring three wine regions located in emerging economies through the lens of the dynamic capabilities framework, this study contributes theoretically and empirically to the wine tourism and wine entrepreneurship literature. Unstructured, face-to-face interviews conducted among 32 Argentinian and Chilean wineries revealed the effects of and the potential to be gained from infrastructure, socioeconomic, and visitor demographic changes. Moreover, sensing and seizing upon potential opportunities was strongly associated with the above changes. More importantly, preparing for the future through reconfiguration or continuous renewal was illustrated, for instance, through a desire for highly personalised winery experiences. With the increasing globalisation of the wine industry and resulting wine tourism alternatives/substitutes, developing dynamic capabilities becomes crucial for the sustainability of wineries and wine regions. A proposed model based on the research enables understanding and appreciating opportunities and challenges in a dynamic wine tourism environment.